Circadian, weekly, seasonal, and temperature-dependent patterns of syncope aetiology in patients at increased risk of cardiac syncope. Issue 3 (22nd August 2018) - du Fay de Lavallaz, Jeanne; Badertscher, Patrick; Nestelberger, Thomas; Flores, Dayana; Miró, Òscar; Salgado, Emilio; Geigy, Nicolas; Christ, Michael; Cullen, Louise; Than, Martin; Martin-Sanchez, F Javier; Rodriguez-Adrada, Esther; et al.
Abstract: Aims: It is unknown whether cardiac syncope, and possibly also other syncope aetiologies exhibit circadian, weekly, seasonal, and temperature-dependent patterns. Methods and results: We prospectively recorded the exact time, date, and outside temperature of syncope of patients >40 years old presenting with syncope to the emergency department in a diagnostic multicentre study. Two independent cardiologists/emergency physicians adjudicated the final diagnosis based on all information becoming available during clinical work-up including 1-year follow-up. Among 1230 patients, the adjudicated aetiology was cardiac in 14.6%, reflex in 39.2%, orthostatic in 25.7%, other non-cardiac in 9.7%, and unknown in 10.8% of patients. All syncope aetiologies occurred much more frequently during the day when compared with the night ( P < 0.01). While reflex and orthostatic syncope showed a broad peak of prevalence with 80.9% of these events occurring between 4 am and 4 pm, cardiac syncope showed a narrow peak of prevalence with 70.1% of all events occurring between 8 am and 2 pm. A weekly pattern was present for most syncope aetiologies, with events occurring mainly from Monday to Friday ( P < 0.01). Reflex syncope displayed a seasonal rhythm and was more common in winter ( P < 0.01), while cardiac syncope stayed constant over the year. Syncope occurred most often when the outside temperature was coldest. Overall the patterns observed for cardiac syncope were similar to the patterns observed for its differential diagnosis. Conclusion: Syncope aetiologies in patients >40 years old display circadian, weekly, seasonal, and temperature-dependent patterns. Unfortunately, these patterns do not allow to reliably differentiate cardiac syncope from other aetiologies.